The enforcement of EU financial law - Crijns, Jan; Haentjens, Matthias; Haentjens, Rijnhard (London : Bloomsbury Publishing, 2022)
"This book focuses on the enforcement of EU financial law on the national and supra-national levels. Emphasis is laid on the interaction between the EU and national levels (vertical interaction), as well as between the private, administrative, and criminal law levels (horizontal interaction). The book takes a multi-jurisdiction and inter-disciplinary approach and covers a range of issues that are highly topical, such as the new EU Anti-Money Laundering regime, and the ReNEUAL model for administrative law. Over the last few decades, EU financial law has grown exponentially. Virtually all these new rules and regulations require enforcement. However, the EU legislator generally has been reluctant to regulate enforcement at the national level, and often does not prescribe whether enforcement should take place through national criminal, administrative, or private law. This results in both practical and fundamental questions for the legal practitioner and the academic. This book addresses those questions. With contributions by leading academics and senior members of EU and national institutions, the book will be of interest to professionals dealing with financial law in their daily practice such as lawyers, bankers, policy makers, officers at supervisory authorities, and judges, but also for academics interested in fundamental questions of interaction between legal systems"--
1. Enforcement of EU Financial Regulation and Investor Protection / Jan Crijns (Leiden University, the Netherlands), Matthias Haentjens (Leiden University, the Netherlands) and Rijnhard Haentjens (University of Amsterdam, the Netherlands) -- 2. The Implementation and Enforcement of European Financial Regulation / Eddy Wymeersch (University of Ghent, Belgium) -- 3. Some Thoughts on the ratio, Creation and Enforcement of EU Financial Services Regulation in the Area of Private Law / Karl-Philipp Wojcik (Single Resolution Board, Belgium) -- 4. Enforcement of Qualitative Capital Requirements for Banks / Bart Joosen (VU Amsterdam, the Netherlands) -- 5. Administrative Enforcement of European Financial Regulation / Saskia Nuijten (NautaDutilh, the Netherlands) -- 6. The EU Courts as Juges de Droit National in the Single Supervisory Mechanism? / Jouke Tegelaar (Leiden University, the Netherlands) -- 7. Criminal Enforcement of EU Financial Standards / Daan Doorenbos (Stibbe, the Netherlands; Radboud University Nijmegen, the Netherlands) -- 8. Full Cooperation versus the Right Not to Incriminate Oneself: Oil and Water? / Joost Nan (Wladimiroff Advocaten, the Netherlands; Erasmus University Rotterdam, the Netherlands) -- 9. The Enforcement Paradox of the ne bis in idem Principle in EU Criminal Financial Law: Not What It Seems / Rijnhard Haentjens (University of Amsterdam, the Netherlands) -- 10. European Strategies Against Money Laundering: A Critical Overview of Current and Future Enforcement / Silvia Allegrezza (University of Luxembourg) -- 11. Concluding Remarks on Interdisciplinarity and Fairness in Financial Law / Jan Crijns (Leiden University, the Netherlands), Matthias Haentjens (Leiden University, the Netherlands) and Rijnhard Haentjens (University of Amsterdam, the Netherlands).
Includes bibliographical references.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Keywords: Financial institutions -- Law and legislation -- European Union countries; Banks and banking -- Law and legislation -- European Union countries